2015
DOI: 10.1080/09650792.2015.1076731
|View full text |Cite
|
Sign up to set email alerts
|

English language teachers becoming more efficacious through research engagement at their Turkish university

Abstract: While it is generally recognized that teacher research can be a very beneficial form of continuing professional development (CPD), there is still relatively limited research available on the impact this activity has on teachers’ self-efficacy beliefs, which are of interest to educational psychologists because, while being open to constant change, these beliefs influence the way in which knowledge is transformed into action. There is also a relative lack of available research into how teachers develop as resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 32 publications
(54 reference statements)
3
42
1
1
Order By: Relevance
“…Regarding the latter, Wyatt (2016) highlights how focusing on self-directed action research tasks helped Omani English teachers, reflecting and experimenting, grow in practical knowledge and LTSE beliefs longitudinally. Engaging in teacher research as continuing professional development helped Turkish English teachers in Wyatt and Dikilitaş (2016) become more efficacious with regard to the specific tasks that concerned them.…”
Section: Changes Shaped By Language Teacher Educationmentioning
confidence: 99%
“…Regarding the latter, Wyatt (2016) highlights how focusing on self-directed action research tasks helped Omani English teachers, reflecting and experimenting, grow in practical knowledge and LTSE beliefs longitudinally. Engaging in teacher research as continuing professional development helped Turkish English teachers in Wyatt and Dikilitaş (2016) become more efficacious with regard to the specific tasks that concerned them.…”
Section: Changes Shaped By Language Teacher Educationmentioning
confidence: 99%
“…Teacher research can encompass action research (Burns, 2010;Dikilitaş & Griffiths, 2017) and exploratory practice (Allwright & Hanks, 2009;Hanks, 2017) and it is used as continuing professional development in Latin American countries such as Argentina (Banegas, Pavese, Velázquez, & Vélez, 2013), Brazil (Seixas Vial & Kurtz de Souza Welp, 2015, Chile (Burns, Westmacott, & Hidalgo Ferrer, 2016;Smith, Connelly, & Rebolledo, 2014), Mexico (Roux & Mendoza Valladares, 2014) and in other countries, for example Australia (Edwards & Burns, 2016b), China (Wang & Zhang, 2014;Yuan et al, 2016), or Turkey (Wyatt & Dikilitaş, 2015). Previous research reports how future teachers (Villacañas de Castro, 2014) and practising teachers engage in action research to bridge the so-called gap between theory and practice and produce context-responsive answers to their classroom concerns (Edwards & Burns, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example: [You] have the opportunity to look at the things you do in order to improve them, but also to realise…that sometimes, you could do better…things that you do not consider, you can include in your The participants' first presentations of their projects to the university community in September 2016 was a valuable experience for some of them: having the opportunity to reflect on their data as part of developing their presentations was helpful for the writing stage, and it was encouraging to hear other teachers comment on the importance of their topics. Other authors have also noted that in-house presentations can contribute to teacher researchers' sense of identity as researchers (e.g., Edwards & Burns, 2016b;Wyatt & Dikilitaş, 2015). However, the feedback received by one of the participants from her colleagues was rather negative, and she felt that, despite the relatively underdeveloped research culture at the university, her colleagues would have given more credit to more academic, formal presentations.…”
Section: Reflections On the Tarp Pilotmentioning
confidence: 87%
“…Yuan and Lee (2014), noting the impact of facilitative teacher-university researcher partnerships in this process, found that the teachers they worked with in Hong Kong gradually changed their preconceptions about research as they learned more about action research and learned to cope with challenging contextual constraints, which led to professional learning and development. Wyatt and Dikilitaş (2015) found that the three teacher-researchers they studied in Turkey, who all began with low self-beliefs about their abilities to do research, became more efficacious as they engaged in continuing professional development that involved doing research. Mentoring, encouraging, and supporting their autonomy, and providing opportunities for them to present their research all contributed to their development as researchers.…”
Section: Introductionmentioning
confidence: 99%